NEW TECHINQE FOR SOLVIND FINITE LEVEL FUZZY NON-LINEAR INTEGRAL EQUATION (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, non linear finite fuzzy Volterra integral equation of the second kind is considered. The successive approximate method will be used t o solve it, and comparing with the exact solution and calculate the absolute error between exact and approximate method . Some numerical examples are prepared to show the efficiency and simplicity of the method.